Cote d'Ivoire : Second Review Under the Three-Year Arrangement Under the Extended Credit Facility, Request for Modification of Performance Criteria, and Financing Assurances Review-Staff Report; Staff Supplements; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Cote d'Ivoire. (IMF Staff Country Reports; Country Report, 2012)
In recent years, the IMF has released a growing number of reports and other documents covering economic and financial developments and trends in member countries. Each report, prepared by a staff team after discussions with government officials, is published at the option of the member country.